Multi-omics integration reveals the impact of mediterranean diet on hepatic metabolism and gut microbiota in mice with metabolic dysfunction-associated steatotic liver disease - Wang, Zixuan; Chen, Ge; Sun, Xutong; Xiao, Jia; Kong, Lingling; Jiang, Shunshun; Xu, Tingting; Wang, Meijiao; Zhao, Hong (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the effects of the Mediterranean diet (MD) on hepatic metabolism and gut microbiota in mice with metabolic dysfunction-associated steatotic liver disease (MASLD).MethodsC57BL/6 mice were fed a high-fat diet for 12 weeks to induce MASLD, with normal chow (NC)-fed mice as controls. Post-modeling, MASLD mice were randomized into three groups: HF (continued high-fat diet), HF-NC (switched to normal chow), and HF-MD (switched to MD). After 18-week interventions, body/liver weights, serum liver enzymes (ALT, AST), hepatic glycolipid markers (glucose, TC, TG, IBIL, DBIL), inflammatory cytokines (IL-6, TNF-α; ELISA), and histopathology (H&E and Oil Red O staining) were analyzed. Gut microbiota (metagenomic sequencing) and short-chain fatty acids (SCFAs; targeted metabolomics) were profiled.ResultsHigh-fat diet induced MASLD features including obesity, increased abdominal fat mass, hepatic steatosis with lipid droplets, and inflammation. Both HF-NC and HF-MD groups exhibited reduced body weight, liver index, hepatic cytokines, serum enzymes, and improved glucolipid profiles vs. HF group (p < 0.05), with histopathology confirming attenuated steatosis. HF-MD outperformed HF-NC in lowering ALT, AST, IL-6, and TNF-α (p < 0.05). MASLD mice showed gut dysbiosis characterized by decreased diversity, elevated Alistipes, Helicobacter, Mucispirillum, and Chlamydia, reduced SCFAs, and increased branched-chain fatty acids (BCFAs) (p < 0.05). Both dietary interventions partially ameliorated gut dysbiosis in MASLD mice, with the HF-MD group uniquely enriching beneficial taxa including Prevotella, Muribaculum, Duncaniella, and Barnesiella.ConclusionMD alleviates MASLD progression by synergistically improving hepatic metabolic homeostasis and gut microbiota composition, demonstrating superior efficacy over NC in mitigating inflammation, enriching beneficial microbes, and regulating microbial metabolism. These findings highlight MD's potential as a targeted dietary intervention for MASLD.